2002
DOI: 10.1517/14656566.3.11.1599
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment options for acute pain

Abstract: The pain that accompanies surgical procedures remains prevalent and is an aspect of the perioperative experience that generates the greatest concern for patients about to undergo surgery. There is also a growing recognition of the extent that acute painful experiences can lead to longer-term painful consequences, even when tissue healing appears to be complete. The neurobiologic basis of this has been partially elucidated. The key observations are that multiple sites and multiple receptors collectively contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…27 Ushiyama et al 28 observed a relationship between sympathetic activation, surgical stress, and noncardiac postoperative complications such as leakages of anastomoses, delays in wound healing due to wound inflammation, and infections. 30,31 HRV has also been applied in monitoring sympathetic neural drive blockade by analgesia, revealing the superiority of thoracic epidural analgesia to patient-controlled analgesia. 29 This protocol involving systemic medication and wound infiltration with local anesthetic has been adopted by our team as a procedure-specific postoperative pain management plan recommended by experts.…”
Section: Discussionmentioning
confidence: 99%
“…27 Ushiyama et al 28 observed a relationship between sympathetic activation, surgical stress, and noncardiac postoperative complications such as leakages of anastomoses, delays in wound healing due to wound inflammation, and infections. 30,31 HRV has also been applied in monitoring sympathetic neural drive blockade by analgesia, revealing the superiority of thoracic epidural analgesia to patient-controlled analgesia. 29 This protocol involving systemic medication and wound infiltration with local anesthetic has been adopted by our team as a procedure-specific postoperative pain management plan recommended by experts.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy is through the use of nonpungent agents such as sevoflurane; these nonpungent VGAs have no activity at TRPA1 (Matta et al, 2008) and significantly less activity at TRPV1 compared with pungent VGAs. Another strategy is the use of preemptive analgesia with local anesthetics and opioids (Wilder-Smith, 2000;Gottschalk et al, 2002). However, although these drugs would inhibit C-fiber discharge and transmission in the spinal cord, they would not prevent direct activation of TRPV1 and TRPA1 and the resultant neuropeptide secretion at nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…The unpredictable, recurrent, intense, and frequently persistent nature of pain associated with SCD poses a difficult challenge in terms of management. There is a growing recognition that acute painful experiences can lead to long‐term painful consequences, even when the inflammatory and hemolytic process accompanying the VOE appears to have resolved [4]. The severity of acute painful episodes varies widely and a small subset of patients had frequent hospitalizations.…”
Section: Introductionmentioning
confidence: 99%